Perspectives on online engagement: A study about civic participation - Pimentel, Marta Stamm Matos (2020)
Civic participation has been decreasing, and given the importance of representation for democratic societies, it is imperative to understand why this reduction is occurring. Why do some people participate while others do not? What factors affect citizens’ participation? Based on previous studies that focus on youth involvement and political engagement, and considering worldwide success cases, the present dissertation focuses on a qualitative research exploring online participation through the analysis of a case study of the Participa platform. Key findings such as the value of transparency for online participation and the motivational capacity of political interests allow for a broader understanding of what affects participation in online platforms. Understanding these factors can allow societies to aim for a more inclusive environment; with enough engagement to attract masses and guarantee long term participation (Smith, Lister, Middleton & Cox, 2005). Future studies can consider cultural differences and resort to a quantitative approach. Increasing participation levels could get societies to become more proactive and united, bringing hope that future generations reach a brighter future more tolerant and open to change.